Endoplasmic reticulum protein 29 (ERp29), a protein related to sperm maturation is involved in sperm-oocyte fusion in mouse - Ying, Xiaoqian (BioMed Central, 2010)
BACKGROUND: Sperm-oocyte fusion is a critical step in fertilization, which requires a series of proteins from both spermatozoa and oocyte to mediate membrane adhesion and subsequent fusion. A rat spermatozoa membrane protein is endoplasmic reticulum protein 29 (ERp29), which significantly increases on the sperm surface as well as in the cytoplasm of epididymal epithelia from caput to cauda as the sperm undergo epididymal maturation. Moreover, ERp29 facilitates viral infection via mediating membrane penetration. We determined if in addition to promoting sperm maturation ERp29 may also play a role in facilitating gamete fusion during the fertilization process. METHODS: Laser scanning confocal microscopy (LSCM) and Western blot analysis were employed to probe for ERp29 protein in BALB/c mouse epididymal and acrosome-reacted spermatozoa. We prepared rabbit polyclonal antibodies against mouse recombinant ERp29 (rERp29) to characterize: 1) fertilization rate (FR); 2) fertilization index (FI); 3) sperm motility and 4) acrosome reaction (AR). RESULTS: Confocal microscopy indicated that ERp29 was partially localized at the sperm head of the epididymal caput as well as over the whole head and part of the principal piece of the tail region from the epididymal cauda. However, when the acrosome reacted, ERp29 remained in the equatorial and post-acrosomal regions of the sperm head, which is the initial site of sperm-oocyte membrane fusion. Such localization changes were confirmed based on the results of Western blot analysis. Furthermore, the antibodies against mouse rERp29 inhibited the spermatozoa from penetrating into the zona pellucida (ZP)-free oocytes. The functional blocking antibodies reduced both mouse sperm-oocyte FR and FI at concentrations of 100 and 200 micro g/ml compared with pre-immunized rabbit IgG or with anti-mouse recombinant bactericidal/permeability-increasing protein (BPI, a sperm surface protein unrelated to sperm-oocyte fusion) antibodies (100 micro g/ml), but they had no effect on sperm motility and AR. CONCLUSION: This study demonstrates that ERp29 on mouse spermatozoa membrane changes during epididymal transit and AR. Accordingly, in mice this protein may be one of the important factors involved in sperm fertilization by facilitating sperm-oocyte membrane fusion.